Effect of training system on the incidence of Stigmina carpophila and fruit size and weight of European plum (Prunus domestica) - Molnár, B.; Holb, I. J. (International Journal of Horticultural Science, 2023)
In a two-year study (2017-2018), the aim was to determine the incidence of shot hole disease (Stigmina carpophila) on plum cultivar ’Čačanska lepotica’ in four different training systems with tree spacings of 4 x 1.5, 4 x 2, 5 x 2.5 and 6 x 3 m. Fruit size (width and length) and fruit weight were also assessed during harvest of fruit in the four training system. Cultivar ’Čačanska lepotica’ was susceptible to shot hole disease and showed shot hole symptoms in both years and in all training systems. In 2017, the highest disease incidence was observed in the 4 x 1.5 m plot (34% in June and 85% at the end of September). In June and July, the 6 x 3 m training system had the lowest disease incidence. In August and September, the 5 x 2.5 m training system had the smallest incidences of the disease among the training systems. In 2018, except for one assessment date (18 August) the 4 x 1.5 m plot had higher incidences than the other three training systems. Training system and years had almost no effect on fruit size, but there were some differences in fruit weight among the training systems.